Kemampuan Berpikir Kreatif Siswa SMK dalam Pemecahan dan Pengajuan Masalah Open Ended Materi Barisan dan Deret - Mahmudah, Inani; Titin Masfingatin; Astuti, Indra Puji (Absis: Mathematics Education Journal, 2024)
Vocational high school students need the ability to think creatively to face the challenges of the world of work in the 21st century. Creative thinking skills can be developed through open ended problem solving and problem posing activities. This study aims to describe the creative thinking skills of vocational students in solving and posing open ended problems on sequences and series material. This study uses a type of qualitative research. The subjects of this study were students of class X Office Management 1 (MP-1) at SMK Negeri 1 Geger for the 2022/2023 academic year. Data collection techniques using tests and interviews. Testing the validity of the data using triangulation techniques. Data analysis includes data reduction, data presentation and drawing conclusions. The results of this study are: Vocational school students' creative thinking abilities in solving open-ended problems include indikators of fluency, flexibility and novelty. Novelty is the least likely to appear. Vocational school students' creative thinking abilities in posing open-ended problems include indikators of fluency and flexibility, while indikators of novelty have not yet appeared in posing problems. When posing problems, vocational school students tend to be inspired by previously solved problems. Based on the results of this research, teachers are expected to be able to present open-ended problems in learning so that students' creative thinking abilities can develop well.